Hysteretic behavior of SMA energy dissipater with shape memory effect induced by heating recovery. (1st June 2023) - Gong, Zhao-Hui; Shi, Hai-Rong; Zhang, Jin; Wang, Chun-Lin; Meng, Shao-Ping
Abstract: The buckling restrained energy dissipater is one small axial yield type energy dissipation device usually attached to the prefabricated structure to improve seismic performance. In this paper, a shape memory alloy bamboo-shaped energy dissipater (SMA-BED) was proposed, which used bamboo-shaped SMA rod as the energy dissipation core. The special shape memory effect of SMA material was expected to recover the residual deformation, and the outer restraining tube was used to prevent the core buckling and instability. The tests of 8 SMA-BED specimens were completed to compare the effect of repeated loadings on hysteretic behavior. The results showed that all specimens exhibited stable and full hysteretic loops. After loading, the average deformation recovery ratio of all specimens was about 97.9% by heating in a water bath and cooling to room temperature. The load-displacement curve obtained by reloading the specimen basically coincided with the previous curve, and the results were consistent after repeated 3 loading times. The compression and deformation modes of the SMA-BED core with different construction forms were analyzed theoretically, meanwhile a lateral displacement computation model of the yielding part was proposed, which could better estimate the contact between yielding part and restraining tube. Highlights: Shape memory effect was expected to recover the residual deformation. High deformation recovery ratio achieved by the water-bath heating and cooling. SMA-BED had excellent recoverability and energy dissipation capacity. The proposed computation model can better evaluate the experimental results.